Differential effects of ankle constraints on foot placement control between normal and split belt treadmills - Hos, M.; van Iersel, L.; van Leeuwen, A.M.; Bruijn, S.M. (Journal of Biomechanics, 2022)
Mediolateral ankle moment control contributes to gait stability. Ankle moments can be constrained by walking with a shoe with a ridge underneath the sole, narrowing the mediolateral support surface. In our previous study, such ankle moment constraints resulted in an increased step width and a decrease in the degree of foot placement control, as defined by the percentage of variance in foot placement that can be explained by CoM state. However, since our previous study was performed on a split-belt treadmill and the narrow ridge could fit inside the gap between the belts, it is not evident whether these effects can be attributed to the constrained ankle moment control or to avoidance of this gap. Therefore, we investigated if the effects of ankle moment constraints are dependent on whether participants walk on a normal treadmill or a split-belt treadmill. We included fourteen healthy young adults. Walking with constrained ankle moment control resulted in a wider step width on both treadmills. Yet, the increase in step width was larger on the split-belt treadmill compared to on the normal treadmill. We only found a decreased degree of foot placement control on the split-belt treadmill, whilst the degree of foot placement control increased on the normal treadmill. We conclude that the effects of ankle moment constraints reported in our previous study were confounded by the use of a split-belt treadmill. For future research, we recommend using a normal treadmill whenever possible, because the gap in a split-belt treadmill might affect gait parameters.